Desarticulaciones (2010) / En breve cárcel (1981). In between writing and life: Sylvia Molloy, the contaminated writing of a lateral criticism - Cróquer Pedrón, Eleonora (Universidad Nacional del Litoral, 2020)
In relation to Desarticulaciones (2010) and En breve cárcel (1981) by Sylvia Molloy, this article focuses on the knotting between writing and life that makes the author’s writing contaminated, the subjective «truth» that they compromise and the knowledge between semiotic and analytical that incorporate about the link between experience, subjectivity and language. Above the stagnant categories of criticism and fiction, among which life frames a relationship of communicating vessels, and beyond the autobiographical trace that is not synthesized in a testamentary history of the subject involved in it, it is about identifying in the places from this knotting the expression of a «lateral» criticism: oblique, marginal, border. That is to say, the practice of reading and intellectual intervention of an eccentric authorship that crystallizes between the setbacks of the academic essay and the profane forms of the minor. Conceived from that position, and protected by the knowledge that this way communicates, the deep subjective implication that Molloy’s writing implies, that form of the «truth» that the affection inscribes in the writing of those who risk it, does not leave to disturb the reader, moved and disconcerted by the intensity of what he reads.